Analisis Kemampuan Berpikir Kritis Matematis Siswa Ditinjau dari Motivasi Belajar dan Self Confidence - Eka Putri, Shabrina; Maryono, Iyon; Sugilar, Hamdan; Safitri Haryadi, Risya (Gunung Djati Conference Series, 2025)
This study aims to examine students' mathematical critical thinking ability in relation to their learning motivation and self-confidence. The research sample consists of 18 ninth-grade students from a private junior high school in Bandung. The approach used in this study is a quantitative approach with a descriptive quantitative method. This study employs two research instruments. The first is a test used to measure critical thinking skills in the form of a posttest. The second is a questionnaire to assess students' learning motivation and self-confidence. Based on the results, it can be concluded that: 1) Higher learning motivation is positively correlated with higher critical thinking ability. 2) Higher self-confidence is positively correlated with higher critical thinking ability.